Peran Guru PJOK dalam Pembentukan Karakter Peserta Didik Sekolah Menengah Pertama Se-Kecamatan Martapura - Zaidan, Wildan; Rakhman, Arie; Amirudin, Akhmad (MAN Insan Cendekia Jambi, 2025)
The aim of this research is to determine the role of Physical Education, Sports, and Health (PJOK) teachers in the character development of junior high school students in Martapura District. The background of this research is the high levels of bullying and the decline in morals among the youth, indicating that schools must play an active role in instilling character values. This research was conducted using a descriptive quantitative method with total sampling techniques. The samples in this study were twelve PJOK teachers from six junior high schools in Martapura District. The research instrument was a closed questionnaire using a Likert scale that encompassed motivation, role modeling, and inspiration. According to the research findings, the majority of teachers play a significant role in building students' character. According to the research findings, most teachers have a significant role in building students' character. The majority of teachers are categorized as always (58%), and (42%) are in the never category. The conclusion of this research is that physical education teachers have a significant role in building students' character.